Atmospheric Pressure Tornado Plasma Jet of Polydopamine Coating on Graphite Felt for Improving Electrochemical Performance in Vanadium Redox Flow Batteries - Chen, Song-Yu; Kuo, Yu-Lin; Wang, Yao-Ming; Hsu, Wei-Mau; Chien, Tzu-Hsuan; Lin, Chiu-Feng; Kuo, Cheng-Hsien; Okino, Akitoshi; Chiang, Tai-Chin (Catalysts, 2021)
The intrinsic hydrophobicity of graphite felt (GF) is typically altered for the purpose of the surface wettability and providing active sites for the enhancement of electrochemical performance. In this work, commercial GF is used as the electrodes. The GF electrode with a coated-polydopamine catalyst is achieved to enhance the electrocatalytic activity of GF for the redox reaction of vanadium ions in vanadium redox flow battery (VRFB). Materials characteristics proved that a facile coating via atmospheric pressure plasma jet (APPJ) to alter the surface superhydrophilicity and to deposit polydopamine on GF for providing the more active sites is feasibly achieved. Due to the synergistic effects of the presence of more active sites on the superhydrophilic surface of modified electrodes, the electrochemical performance toward VO2+/VO2+ reaction was evidently improved. We believed that using the APPJ technique as a coating method for electrocatalyst preparation offers the oxygen-containing functional groups on the substrate surface on giving a hydrogen bonding with the grafted functional polymeric materials.